Is Byzantine studies a colonialist discipline? : toward a critical historiography - Anderson, Benjamin; Ivanova, Mirela (Historian) (ICMA books--viewpoints., 2023)
"A volume of essays by scholars of Byzantine art, history, and literature addressing the entanglements between the academic discipline of Byzantine studies and the practice and legacies of European colonialism"--